1966
DOI: 10.1021/jo01344a037
|View full text |Cite
|
Sign up to set email alerts
|

C-2 Oxyanion Participation in the Base-Catalyzed Cleavage of p-Nitrophenyl β-D-Galactopyranoside and p-Nitrophenyl α-D-Mannopyranoside1

Abstract: p-Nitrophenyl 2-O-methyl-,3-~-galactopyranoside and p-nitrophenyl 2-O-methyl-a-~-mannopyranoside were synthesized and their cleavage reactions were compared with those of p-nitrophenyl @-D-galactopyranoside and p-nitrophenyl a-D-mannopyranoside. The cleavage rates (35-55 ") and products formed from these glycosides (all capable (of a tram-diaxial orientation a t C-1 and C-2) in methanolic and aqueous base solution were studied. Reaction of the glycosides in methanolic sodium methoxide resulted in over-all rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 2 publications
3
35
0
Order By: Relevance
“…This value for the isotope effect is somewhat larger than that accepted for a purely S N~ reaction and probably reflects a small amount of carbonium ion character in the transition state. McClosky and Coleman (1945) and Gasman and Johnson (1966) have found that the yield of 1,6-anhydro-P-~-glucopyranose in the basic hydrolysis of aryl-P-glucosides decreases as the electron-withdrawing character of the aglycone is increased. This is consistent with the supposition that the basic solvolysis of G P involves partial carbonium ion character and that the extent of this is a function of the leaving group.…”
Section: Discussionmentioning
confidence: 99%
“…This value for the isotope effect is somewhat larger than that accepted for a purely S N~ reaction and probably reflects a small amount of carbonium ion character in the transition state. McClosky and Coleman (1945) and Gasman and Johnson (1966) have found that the yield of 1,6-anhydro-P-~-glucopyranose in the basic hydrolysis of aryl-P-glucosides decreases as the electron-withdrawing character of the aglycone is increased. This is consistent with the supposition that the basic solvolysis of G P involves partial carbonium ion character and that the extent of this is a function of the leaving group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of epoxide intermediates has been proposed to accelerate nonenzymatic decomposition of activated glycosides with a 1,2-trans arrangement under basic conditions (Fig. 6B) (41,42), and nonenzymatic opening of epoxides in a hexose is accelerated by participation of a nearby ester substituent (Fig. 6C) (43)(44)(45).…”
Section: Toward the Mechanism Of Unsaturated Glucuronyl Hydrolasementioning
confidence: 99%
“…Interestingly, there is compelling evidence in support of neighboring group participation by a glycoside 2-hydroxyl and 1,2-anhydro sugars as intermediates in the alkaline cleavage of 1,2-trans glycosides and glycosyl fluorides. This data includes the wellknown differences in the rate of alkaline hydrolysis of 1,2-cis-versus 1,2-trans-glycosides, the reduced rate of alkaline hydrolysis of otherwise identical 2-alkylated 1,2-transglycosides 2 , and retention of anomeric stereochemistry in the alkaline methanolysis of 1,2trans-glycosyl fluorides whereas 2-alkylated 1,2-trans-glycosyl fluorides react with inversion 3 . Kinetic isotope effects for the alkaline hydrolysis of 4-nitrophenyl -Dmannopyranoside provided compelling evidence for neighboring-group participation by a C2-oxyanion 4 , and methods have recently been developed allowing for synthesis of 1,2anhydro sugars 5,6 .…”
mentioning
confidence: 99%